STRATEGY ALIGNMENT: KEY FACTORS FOR EFFECTIVE STRATEGY IMPLEMENTATION: A Review Of Conceptual And Empirical Literature - Iskandar, Andy; Ardianto, Eka (Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aimed to conduct a literature review to determine the reason behind the difficulty of strategy implementation. To achieve this objective, 36 articles were collected from 1980 to June 2023 from previous literature reviews and the results of searching several other leading journals. The result showed that it is necessary to add a strategy alignment category as an important bridge between formulation and implementation. Furthermore, 6 important factors in strategy alignment need to be considered as a key success for effective implementation. The article contributes a theoretical strategy alignment framework and guidance questions useful to practitioners to ensure that the process runs well, thereby allowing an effective strategy implementation.